A novel MTPA and flux weakening method of stator flux oriented control of PMSM. Issue 3 (2nd July 2021) - Wen, Yuliang; Zheng, Hanfeng; Yang, Fang; Zeng, Xiaofan
Abstract: Permanent magnet synchronous motor (PMSM) has the advantages of high efficiency, high power density and high reliability. It has been widely used in electric vehicles, rail transit, industrial transmission and other fields. Compared with the traditional PMSM control strategy, the Indirect stator-quantities control (ISC) of low torque ripple induction motor has high dynamic response performance in the whole speed range, with high stability and strong security. However, due to the inherent characteristics of PMSM, there are still some difficulties in applying ISC strategy, such as solving the load angle corresponding to the current torque, realizing the maximum torque per ampere (MTPA) control and flux weakening control method in the stator field oriented control algorithm of PMSM. In this paper, theoretical analysis and discussion are carried out for the above difficulties, and an indirect stator vector control (ISC) method for PMSM is proposed. Finally, combined with the electric drive application platform of electric vehicle, the simulation and experimental results verify that the proposed ISC control strategy of PMSM also has good dynamic and steady-state performance in the whole speed range.